2016
DOI: 10.1007/s00464-016-5311-1
|View full text |Cite|
|
Sign up to set email alerts
|

EUS-guided gastroenterostomy is comparable to enteral stenting with fewer re-interventions in malignant gastric outlet obstruction

Abstract: EUS-GE may be ideal for malignant GOO with comparable effectiveness and safety to ES while being associated with fewer symptom recurrence and requirements for re-intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
177
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 180 publications
(201 citation statements)
references
References 24 publications
8
177
6
Order By: Relevance
“…Although no mortality has been reported, adverse events such as peritonitis and bleeding have been reported. When compared to enteral stenting, the rates of reintervention for stent dysfunction appears to be lower (6.1% vs 30.3%) for patients undergoing EUS‐guided gastroenteric anastomosis …”
Section: Current Clinical Applicationsmentioning
confidence: 97%
See 1 more Smart Citation
“…Although no mortality has been reported, adverse events such as peritonitis and bleeding have been reported. When compared to enteral stenting, the rates of reintervention for stent dysfunction appears to be lower (6.1% vs 30.3%) for patients undergoing EUS‐guided gastroenteric anastomosis …”
Section: Current Clinical Applicationsmentioning
confidence: 97%
“…When compared to enteral stenting, the rates of reintervention for stent dysfunction appears to be lower (6.1% vs 30.3%) for patients undergoing EUS-guided gastroenteric anastomosis. 22,23 Altered surgical anatomy…”
Section: Gastric Outlet Obstructionmentioning
confidence: 99%
“…102 paring enteral stenting with EUS-GE revealed comparable clinical success, with 83.3% in the EUS-GE arm and 69.9% in the enteral stent cohort (P = 0.2). 103 Most notably, those undergoing EUS-GE had a lower rate of stent obstruction (3.3% EUS-GE vs 26.9%) or need for re-intervention (3.3% vs 46.2% enteral stent). 103 Celiac plexus neurolysis and celiac ganglion neurolysis…”
Section: Eus-guided Anastomosismentioning
confidence: 90%
“…103 Most notably, those undergoing EUS-GE had a lower rate of stent obstruction (3.3% EUS-GE vs 26.9%) or need for re-intervention (3.3% vs 46.2% enteral stent). 103 Celiac plexus neurolysis and celiac ganglion neurolysis…”
Section: Eus-guided Anastomosismentioning
confidence: 90%
“…EUS-guided interenteric anastomosis has been described mainly in patients with malignant gastric outlet obstruction, with high technical and clinical success rates 1, 2, 3. In comparison with enteral stenting, EUS-guided gastroenterostomy (GE) showed comparable safety and fewer symptom recurrences 4 . Another recently published study comparing endoscopic GE versus surgical GE showed noninferiority of endoscopic GE in terms of clinical success, and there was a trend toward fewer adverse events 5 …”
mentioning
confidence: 99%